Credit Risk Mitigation and Loan Performance of Financial Institution: A Case Study of Zigama Credit Saving Society - Kubwimana, Josiane Hadidja; Kengere, Athanas Osiemo (Journal of Finance and Accounting, 2023)
Despite the fact that Rwanda has cooperatives and financial institutions functioning since the 1970s, savings and credit cooperatives have not performed as expected in terms of having an impact on people’s lives with the intention of enhancing the wellbeing of its participants, ZCSS was established in 1998. The ZCSS seek to gather funds from its members in order to offer loans to them at a low interest rate. The study’s three specific objectives—To assess how risk identification is carried and affect loan performance, to evaluate how risk is assessed, monitored and affect loan performance and to analyze the effectiveness of financial tools for enhancing loan performance and minimizing potential losses at Zigama are designed to help evaluate risk mitigation as a financial tool to improve loan performance. The study adopted a descriptive and correlational research design. Stratified and simple random sampling was utilized to choose the population to be sampled and the individuals for data collection. The research’s target population included operational managers, credit officers, finance managers, and loan officers from several Zigama CSS Branches, totaling 41 respondents. Questionnaire was utilized for primary data gathering desirable for the research. Study was conducted in Remera as ZCSS Headquarters, Huye, Karongi, Nyamata and Byumba branches where 5 Point Likert scale questionnaires was adopted. Data was analyzed in form of descriptive and inferential statistics. Because random sampling was utilized to choose the respondent, every participant was given an equal chance of being selected. Questionnaire was used to select primary data and using SPSS Version 27 to analyze data in terms of quantitative method. The study findings regarding to the gender of respondents reveal that, majority of the respondents were male who constituted 82.93% of the total respondents while the female was 17.07%. Research revealed that risk Identification alone has a 21.7% effect on Loan performance at Zigama CSS. Research also revealed that 27.9% of risk assessment had an effect on loan performance at Zigama CSS and Risk monitoring found to have no significant effect on loan performance where findings depicted only 2.9% whereas 97.1% influenced by other factors. The effects for all the three financial tools (risk identification, risk assessment, risk Monitoring) on loan performance was computed to be at an R Squared coefficient of 0.441. It meant that the financial tools accounted for 44.1% of the variation in loan performance could be explained by the three (risk identification, risk assessment, risk Monitoring) belonging to credit risk mitigation. This denotes a low rate of influence that the tools (variables) have on loan performance. the study concluded that Zigama CSS used credit risk mitigation to a very great extent which resulted into not only reduction in default rates among bank clients but also led to significant decrease in level of non-performing loans. Key words: Risk mitigation, Loan performance, financial tool, Zigama CSS, Loan portfolio, Non-performing loans.